Development and validation of the Scleroderma Clinical Trials Consortium Damage Index (SCTC-DI): a novel instrument to quantify organ damage in systemic sclerosis. Issue 6 (30th June 2019) - Ferdowsi, Nava; Huq, Molla; Stevens, Wendy; Hudson, Marie; Wang, Mianbo; Tay, Tien; Burchell, Jodie L; Mancuso, Sam; Rabusa, Candice; Sundararajan, Vijaya; Prior, David; Proudman, Susanna M; et al.
Abstract : Objective: We sought to develop the first Damage Index (DI) in systemic sclerosis (SSc). Methods: The conceptual definition of 'damage' in SSc was determined through consensus by a working group of the Scleroderma Clinical Trials Consortium (SCTC). Systematic literature review and consultation with patient partners and non-rheumatologist experts produced a list of potential items for inclusion in the DI. These steps were used to reduce the items: (1) Expert members of the SCTC (n=331) were invited to rate the appropriateness of each item for inclusion, using a web-based survey. Items with >60% consensus were retained; (2) Using a prospectively acquired Australian cohort data set of 1568 patients, the univariable relationships between the remaining items and the endpoints of mortality and morbidity (Physical Component Summary score of the Short Form 36) were analysed, and items with p<0.10 were retained; (3) using multivariable regression analysis, coefficients were used to determine a weighted score for each item. The DI was externally validated in a Canadian cohort. Results: Ninety-three (28.1%) complete survey responses were analysed; 58 of 83 items were retained. The univariable relationships with death and/or morbidity endpoints were statistically significant for 22 items, with one additional item forced into the multivariable model by experts due to clinical importance, to create a 23-item weighted SCTC DI (SCTC-DI). The SCTC-DI was predictive of morbidity and mortality in the external cohort. Conclusions: Through the combined use of consensus and data-driven methods, a 23-item SCTC-DI was developed and retrospectively validated.